Pendidikan, Human Capital ataukah Signaling? Studi Kasus Indonesia - Fahmi, Mohamad; Mulyono, Yeni Oktavia (UI Scholars Hub, 2015)
This study aims to test whether the behavior of Indonesian people in determining education is the manifestation of human capital theory or signaling theory. Using the ordinary least square (OLS) model and the Indonesian Family Life Survey (IFLS) 2007 data, we find that both theories mutually have effect to influence the behavior of Indonesian people to determine their education.